Foot Hydrotherapy Air Garam Efektif dalam Peningkatan Kualitas Tidur Pada Lansia - I Ketut Gama; Ketut Sudiantara; I Wayan Mustika; I Wayan Suardana (FORIKES, 2023)
Aging is a process of decreasing the body's immune system which causes changes in physiological function, namely the need for sleep which has an impact on sleep quality. The aim of this research was to determine the effect of foot hydrotherapy with salt water on improving sleep quality in the elderly. The design of this research was one group pre-test and posttest. The research subjects were 25 elderly people aged 60-74 years in the Working Area of South Denpasar Public Health Center I who were selected using a total sampling technique. Sleep quality data was collected by filling in the Pittsburg Sleep Quality Index (PSQI) questionnaire, then analyzed using the Wilcoxon test. The results showed that 25 people experienced poor sleep quality before being given foot hydrotherapy with salt water and after therapy there were 16 people with good sleep quality. The p value of the comparison test was 0.000. It was concluded that foot hydrotherapy with salt water had an effect on improving the sleep quality of the elderly. It is hoped that foot hydrotherapy with salt water can be used as an alternative action in dealing with complaints of difficulty sleeping in the elderly.Keywords: hydrotherapy; salt water; sleep quality ABSTRAK Penuaan merupakan proses penurunan daya tahan tubuh yang menyebabkan perubahan fungsi fisiologis yaitu kebutuhan tidur yang berdampak pada kualitas tidur. Tujuan penelitian ini adalah mengetahui pengaruh foot hydrotherapy dengan air garam terhadap peningkatan kualitas tidur pada lansia. Rancangan penelitian ini adalah one group pre-test and posttest. Subjek penelitian adalah 25 lansia dengan usia 60-74 tahun di Wilayah Kerja Puskesmas I Denpasar Selatan yang dipilih dengan teknik total sampling. Data kualitas tidur dikumpulkan melalui pengisian kuesioner Pittsburg Sleep Quality Index (PSQI), lalu dianalisis dengan uji Wilcoxon, Hasil penelitian menunjukkan bahwa 25 orang mengalami kualitas tidur buruk sebelum diberikan foot hydrotherapy dengan air garam dan sesudah terapi ada 16 orang dengan kualitas tidur baik. Nilai p dari uji perbandingan adalah 0,000. Disimpulkan bahwa foot hydrotherapy dengan air garam berpengaruh untuk mingkatkan kualitas tidur lansia. Diharapkan foot hydrotherapy dengan air garam dapat dijadikan sebagai alternatif tindakan dalam menangani keluhan sulit tidur pada lansia.Kata kunci: hydrotherapy; air garam; kualitas tidur